Cellular differentiation, hormonal gradient, and molecular alternation between the division zone and the elongation zone of bamboo internodes. Issue 5 (18th September 2022) - Guo, Lin; Wang, Chunyue; Chen, Jin; Ju, Ye; Yu, Fen; Jiao, Chen; Fei, Zhangjun; Ding, Yulong; Wei, Qiang
Abstract: Bamboo differentiates a cell division zone (DZ) and a cell elongation zone (EZ) to promote internode elongation during rapid growth. However, the biological mechanisms underlying this sectioned growth behavior are still unknown. Using histological, physiological, and genomic data, we found that the cell wall and other subcellular organelles such as chloroplasts are more developed in the EZ. Abundant hydrogen peroxide accumulated in the pith cells of the EZ, and stomata formed completely in the EZ. In contrast, most cells in the DZ were in an undifferentiated state with wrinkled cell walls and dense cytoplasm. Hormone detection revealed that the levels of gibberellin, auxin, cytokinin, and brassinosteroid were higher in the DZ than in the EZ. However, the levels of salicylic acid and jasmonic acid were higher in the EZ than in the DZ. Transcriptome analysis with qRT‐PCR quantification revealed that the transcripts for cell division and primary metabolism had higher expression in the DZ, whereas the genes for photosynthesis, cell wall growth, and secondary metabolism were dramatically upregulated in the EZ. Overexpression of a MYB transcription factor, BmMYB83, promotes cell wall lignification in transgenic plants. BmMYB83 is specifically expressed in cells that may have lignin deposits, such as protoxylem vessels and fiber cells. Our results indicate that hormone gradient and transcriptome reprogramming, as well as specific expression of key genes such as BmMYB83, may lead to differentiation of cell growth in the bamboo internode.